Peran Inovasi Teknologi dalam Mendukung Akselerasi Pengembangan Unggas Lokal di Indonesia - Zulfanita Zulfanita; Rinawidiastuti Rinawidiastuti; Priyono Priyono (Universitas Muhammadiyah Purworejo, 2021)
Currently, local poultry, especially native chickens, have good prospects, along with various diversifications in poultry products. The management of local poultry which is cultivated intensively and commercially, requires the support of effective and efficient technological innovation so that it will be able to increase the production and productivity of local poultry. One of the local poultry innovations that has been launched based on the Decree of the Minister of Agriculture of the Republic of Indonesia, namely Chicken KUB. The development of superior KUB chickens from research results with high production capabilities needs to be supported by economic feasibility in order to be sustainable. The massive KUB chicken innovation dissemination to various regions in the long term will be able to contribute to the acceleration of the development of local poultry in Indonesia. Policy support through the implementation of a strategy to regulate the continuity of seed sources, institutions, application of good management practices, and improvement of performance and market structure needs to be supported by all parties to improve the bargaining position of competitive local poultry in Indonesia.